2009
DOI: 10.1142/s0219635209002307
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Dendrites in the Functional Activity of the Central Neuron Controlling Goldfish Behavior

Abstract: The structural mechanisms that control the neuronal functional activity maintaining the brain functional asymmetry were studied using the relationship between the function and structure of goldfish Mauthner neurons (MNs) responsible for fish motor asymmetry as a model. It was shown for the first time that the dominant activity in one of the two counter neurons symmetrically situated in the medulla oblongata directly correlates with changes in its integral volume and is inversely regulated by the size of its ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the poecilid, Girardinus metallicus, the directional bias for right or left turns in a detour test positively correlate with head incline asymmetry, but negatively with a fast-escape response test (Matsui et al, 2013). Fast-start startle responses are controlled by the mauthner neurons and several studies have revealed that the direction of the startle response is correlated with the size of the mauthner neuron on the left of right side of the body (eg Moshkov et al, 2009). Dadda et al (2010a,b) for example found that strongly lateralised fish showed higher escape reactivity…”
Section: Laterality and Swimming/schooling Behaviourmentioning
confidence: 99%
“…In the poecilid, Girardinus metallicus, the directional bias for right or left turns in a detour test positively correlate with head incline asymmetry, but negatively with a fast-escape response test (Matsui et al, 2013). Fast-start startle responses are controlled by the mauthner neurons and several studies have revealed that the direction of the startle response is correlated with the size of the mauthner neuron on the left of right side of the body (eg Moshkov et al, 2009). Dadda et al (2010a,b) for example found that strongly lateralised fish showed higher escape reactivity…”
Section: Laterality and Swimming/schooling Behaviourmentioning
confidence: 99%
“…Three-dimensional reconstruction of motoneurons. Three-dimensional reconstruction of the motoneurons and reference structures was performed using serial histological slices according to the method previously described [28][29][30]. The diameters of the soma and nucleus were determined on panoramic images of histological slices using Adobe Photoshop and PTGui v.9.1.8 Pro (USA).…”
Section: Bioethicsmentioning
confidence: 99%